The strategy of Islamic banks and its impact on financing small industry in Libya: A case study of Jumhuriah Bank / Mustfa A. Muftah - Mustfa , A. Muftah (2018)
This research focuses on studying the impact of Islamic banks’ strategy on achieving economic development in Libya, and focuses on assessing the impact of these banks’ policies in financing the small projects as they play a vital role in contributing to the economic development in Libya. The nature of the research necessitated that the analytical descriptive methodology be followed in the study of the subject. Also, a questionnaire was developed in order to collect the necessary data from a sample of (272) employees of the Jumhuriah (Republic) Bank in Libya. The study reached a set of conclusions, most prominent of which is that there exists in Libya a real system of the Islamic banking financing of small projects being implemented that is desirable by the Libyan public in general and much needed as well by the small enterprises in particular. The study also showed the positive impact of the banks’ strategy towards economic development on the success of the financing of small projects, although the implementation of financing the small projects is still fraught with several obstacles and difficulties, both at the level of entrepreneurs and at the level of banking policies and strategies.